2017
DOI: 10.17925/usor.2017.10.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Infections—Challenges in Diagnosis and Update on Management

Abstract: Bennie H Jeng is Professor and Chair of the Department of Ophthalmology and Visual Sciences at the University of Maryland School of Medicine. He earned his bachelor’s degree summa cum laude from Washington University and his MD from the University of Pennsylvania School of Medicine. He then completed his ophthalmology residency and chief residency at the Cole Eye Institute of the Cleveland Clinic, which was followed by a fellowship in cornea and external diseases at the Francis I. Proctor Foundation/University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Nearly all patients who recently visited the Madang Provincial Hospital Eye Clinic reported that they only sought for eye care services when their vision was threatened ( 36 ). Corneal ulcers and keratitis are potential sight threatening morbidities ( 10 , 37 , 38 ), therefore it is necessary that the public are well educated about the benefits of protective eyewear and timely reporting of eye problems to prevent blindness associated with cornea disorders as this may lead to significant loss of productivity in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all patients who recently visited the Madang Provincial Hospital Eye Clinic reported that they only sought for eye care services when their vision was threatened ( 36 ). Corneal ulcers and keratitis are potential sight threatening morbidities ( 10 , 37 , 38 ), therefore it is necessary that the public are well educated about the benefits of protective eyewear and timely reporting of eye problems to prevent blindness associated with cornea disorders as this may lead to significant loss of productivity in the country.…”
Section: Discussionmentioning
confidence: 99%